Magnetic and electronic properties of Cr2Ge2Te6 monolayer by strain and electric-field engineering - Wang, Kangying; Hu, Tao; Jia, Fanhao; Zhao, Guodong; Liu, Yuyu; Solovyev, Igor V.; Pyatakov, Alexander P.; Zvezdin, Anatoly K.; Ren, Wei (Applied physics letters, 2019)
A two-dimensional ferromagnetic semiconductor Cr2Ge2Te6 (CGT) was recently found to possess extraordinary characteristics and has great potential in the emerging field of spintronics. Using first-principles calculations, we examined the stabilities of this layered system by studying the cleavage energies and phonon dispersion. The ferromagnetic ground state has an in-plane spin polarization and bandgaps of about 0.26 eV by Perdew-Burke-Ernzerhof-van der Waals and 0.91 eV by the Heyd-Scuseria-Ernzerhof functional. Furthermore, we employed strain engineering and an external electric field to control the electronic and magnetic properties. In addition, we studied the magnetic anisotropy energy as well as its modulation under the electric field. We predict the CGT monolayer to be the easy plane ferromagnet, and the perpendicular electric field could affect the ferromagnetic stability along different directions. Our obtained results provide guidance for the potential applications of monolayer CGT for magnetic nanodevices, spintronic, and straintronic applications.